Dampak Keuangan Dan Strategi Usaha Mikro, Kecil dan Menengah Untuk Bertahan Dalam Pandemi Covid-19 - Anggana, Reza Patra; Winata, Indra; Restiany, Devi; Yusdiana, Devie; Suhati, Lisafani; Piliang, Fitri Delimasari (PT. Alahyan Publisher Sukabumi, 2023)
The purpose of this study is to find out and analyze the financial impact caused by the COVID-19 pandemic on the development of MSME business in Indonesia based on the position of MSME credit and strategies for MSMEs in dealing with the COVID-19 pandemic by utilizing information technology and internet networks through digitization. The analytical method used in this study is a qualitative descriptive method. The population in this study is MSMEs in Indonesia. The results of this study are in the form of financial impacts and MSME strategies to survive the COVID-19 pandemic. During the Covid-19 pandemic that hit all parts of the world, it hurt economic growth, with the projection for the global economy to grow at minus 3% based on data from the IMF in 2020. Economic activity in Indonesia has become hampered as a result of PPKM, MSME actors in Indonesia. decreased income. The decline in income makes MSME actors who have credit to financial institutions find it difficult to pay their obligations, especially since there are policies from the Government in financial relaxation, one of which is delaying installment payments and credit restructuring so that the credit position will experience a static phase and even decline due to policy uncertainty and the business climate due to covid-19 pandemic. The majority of MSMEs or as many as 82.9% experienced a negative impact from this pandemic. MSMEs make several efforts to maintain their business conditions. They take several efficiency measures such as: reducing the production of goods/services, reducing working hours and the number of employees, and sales/digital marketing channels.